2019
DOI: 10.3390/molecules24030540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Gene Encoding the Specialized Alanine Decarboxylase in Tea (Camellia sinensis) Plants

Abstract: Theanine, a unique amino acid in Camellia sinensis, accounts for more than 50% of total free amino acids in tea and has a significant contribution to the quality of green tea. Previous research indicated that theanine is synthesized from glutamic acid (Glu) and ethylamine mainly in roots, and that theanine accumulation depends on the availability of ethylamine which is derived from alanine (Ala) decarboxylation catalyzed by alanine decarboxylase (AlaDC). However, the specific gene encoding AlaDC protein remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 57 publications
1
46
0
5
Order By: Relevance
“…Additionally, we found expression of serine decarboxylase (SDC; Spo13254) significantly upregulated in response to high N in roots. Most recently, SDC like gene showing remarkably high expression in young roots under sufficient N has been characterized in tea plants [69]. We performed a BLASTP homology search of the NCBI database.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Additionally, we found expression of serine decarboxylase (SDC; Spo13254) significantly upregulated in response to high N in roots. Most recently, SDC like gene showing remarkably high expression in young roots under sufficient N has been characterized in tea plants [69]. We performed a BLASTP homology search of the NCBI database.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…New genes were defined as those that are present in all members of a monophyletic group but absent from all outgroup species [ 20 ]. Our previous research has shown that AlaDC was a novel enzyme and SDC was the protein most closely related to AlaDC [ 16 ]. In this study, a BLAST search result showed that AlaDC gene was only found in tea plants, while the homologous genes of SDC were widely distributed in monocots and dicots (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Theanine is synthesized from glutamate (Glu) and ethylamine catalyzed by theanine synthetase (TS) mainly in the roots of tea plants [ 11 14 ]. Ethylamine is derived mainly from the alanine decarboxylation catalyzed by alanine decarboxylase (AlaDC) [ 12 , 14 16 ]. A great amount of theanine is accumulated in C. sinensis, but little or no theanine in other species [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations